LANGUAGE STRUCTURE: KEY DIFFERENCES BETWEEN ENGLISH AND UZBEK - Hasanova Sevinch Hotam qizi,; Umarqulova Gulshoda Ibrohimovna,; Toshboyeva Bibinur Komil qizi, (TADQIQOTLAR, 2025)
Abstract This article presents a comprehensive contrastive analysis of the fundamental structural  differences  between  English  and  Uzbek.  It  systematically  explores divergences  across  phonological,  morphological,  and  syntactic  levels,  highlighting how their distinct typological classifications lead to profoundly different grammatical and expressive systems. The analysis aims to provide insights for linguists, language educators,  and  learners  by  outlining  the  core  challenges  and  unique  features encountered when navigating these two distinct linguistic frameworks.